Amorphous Iridium Oxide-Integrated Anode Electrodes with Ultrahigh Material Utilization for Hydrogen Production at Industrial Current Densities - Ding, Lei; Li, Kui; Wang, Weitian; Xie, Zhiqiang; Yu, Shule; Yu, Haoran; Cullen, David A.; Keane, Alex; Ayers, Kathy; Capuano, Christopher B.; Liu, Fangyuan; Gao, Pu‑Xian; et al. (Nano-Micro Letters, 2024)
Herein, ionomer-free amorphous iridium oxide (IrOx) thin electrodes are first developed as highly active anodes for proton exchange membrane electrolyzer cells (PEMECs) via low-cost, environmentally friendly, and easily scalable electrodeposition at room temperature. Combined with a Nafion 117 membrane, the IrOx-integrated electrode with an ultralow loading of 0.075 mg cm−2 delivers a high cell efficiency of about 90%, achieving more than 96% catalyst savings and 42-fold higher catalyst utilization compared to commercial catalyst-coated membrane (2 mg cm−2). Additionally, the IrOx electrode demonstrates superior performance, higher catalyst utilization and significantly simplified fabrication with easy scalability compared with the most previously reported anodes. Notably, the remarkable performance could be mainly due to the amorphous phase property, sufficient Ir3+ content, and rich surface hydroxide groups in catalysts. Overall, due to the high activity, high cell efficiency, an economical, greatly simplified and easily scalable fabrication process, and ultrahigh material utilization, the IrOx electrode shows great potential to be applied in industry and accelerates the commercialization of PEMECs and renewable energy evolution. Highlights: 1 Electrodeposited amorphous IrOx thin electrodes are first developed for proton exchange membrane electrolyzer cells. 2 An ultralow loading of 0.075 mg cm−2 archives superior performance to catalyst-coated membrane (2 mg cm−2). 3 > 96% of catalyst savings and > 42-fold higher catalyst utilization are demonstrated.